An avian equivalent of selective abortion: postlaying clutch reduction under resource limitation. (10th March 2019) - Kloskowski, Janusz
Abstract: Selective elimination of excess offspring with poor fitness prospects may occur prenatally (selective abortion) or postnatally (brood reduction). Postnatal reduction is the dominant strategy, presumably because surplus progeny serves as a hedge against environmental and developmental uncertainty. In birds, its main proximate mechanism is asynchronous hatching, generating within-brood competitive asymmetry. Here, clutch-size reduction via last-egg abandonment was investigated in the asynchronously hatching red-necked grebe in a study area comprising 2 human-managed poorly predictable habitats with distinctly different food supplies. Last-egg abandonment, virtually absent in favorable food conditions, occurred regularly in larger clutches in conditions of brood-stage food scarcity. In the food-poor habitat, the production and body condition of fledglings did not differ between last-egg abandoning and caring pairs. The experimentally prolonged hatching interval increased the egg abandonment rate (irrespective of clutch size), but mainly in food-poor conditions. This is the first demonstration of parental clutch reduction in anticipation of brood-stage food limitation. Last-egg abandonment functions as an equivalent of abortion, as discarded offspring are excluded from the postnatal selection arena. This strategy might have evolved as "best-of-a-bad-job" to reallocate parental resources when a strong mismatch between clutch size and chick survival probability reduced the hedging value of later-laid eggs. Abstract : Parent birds unable to rear all their offspring due to resource limitation may decide not to hatch all of their eggs. I show that red-necked grebes may abandon last eggs when feeding conditions prove unfavorable. Experimentally increased hatching asynchrony resulted in increased last-egg abandonment, but mainly under food shortage. Parental clutch reduction functions as the equivalent of abortion, as discarded offspring are not given a chance to prove their individual quality.